2003
DOI: 10.1002/zoo.10102
|View full text |Cite
|
Sign up to set email alerts
|

Post‐occupancy evaluation of zoo Atlanta's Giant Panda Conservation Center: Staff and visitor reactions

Abstract: which presented an opportunity to evaluate the new giant panda exhibit. The present study documents the reactions of staff and visitors to Zoo Atlanta's Giant Panda Conservation Center by a post-occupancy evaluation (POE). Confidential interviews were conducted with 23 staff, and 145 zoo visitors completed questionnaires. Staff and visitors were asked to assign quality ratings to specific areas of the exhibit, and complete a series of open-ended questions. The findings suggest that staff and visitors evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…This practice has been shown especially effective in the case of school groups (Tofield et al, 2003). Though information about enrichment may easily be presented in signage (Mellen et al, 1998), it also provides an opportunity for staff and volunteers to initiate personal interactions with guests, a sought-after visitor experience (Wilson et al, 2003). Training programs are also a great supplement to naturalistic exhibits.…”
Section: Misconceptionsmentioning
confidence: 97%
See 1 more Smart Citation
“…This practice has been shown especially effective in the case of school groups (Tofield et al, 2003). Though information about enrichment may easily be presented in signage (Mellen et al, 1998), it also provides an opportunity for staff and volunteers to initiate personal interactions with guests, a sought-after visitor experience (Wilson et al, 2003). Training programs are also a great supplement to naturalistic exhibits.…”
Section: Misconceptionsmentioning
confidence: 97%
“…Naturalistic exhibits have also been shown to increase stay time, thus allowing for educational opportunities to occur (Shettel-Neuber, 1988). Today, modern zoos are seen by guests and staff as a place for conservation and education (Reade and Waran, 1996;Tompson, 1989;Wilson et al, 2003;Woods, 2002) and presence of naturalistic exhibits may suggest richer lives for the animals (Price et al, 1994;Shettel-Neuber, 1988).…”
mentioning
confidence: 98%
“…In a primarily theoretical POE, Coe et al [2009] examined the potential needs of all three user groups for great apes exhibits, with a focus on bachelor gorilla exhibits. Additionally, Wilson et al [2003] examined visitor and staff responses to a naturalistic giant panda exhibit, with other reports planned to examine how the animals utilize the space. However, despite this obvious lack of comprehensive analyses, many more evaluations do exist for each user group separately, each representing a partial POE.…”
Section: Zoos and Poementioning
confidence: 99%
“…Shettel‐Neuber [1988] interviewed staff during changes from grotto to naturalistic exhibit and found that staff preferred naturalistic exhibits, despite the additional work required. Wilson et al [2003], in their analysis of a naturalistic giant panda exhibit, also found favorable ratings of the exhibit by staff. The staff provided valuable feedback for improving maintenance of the building and gave suggestions as to how day to day care issues, such as maintenance of animal pools, could be facilitated.…”
Section: Zoos and Poementioning
confidence: 99%
“…Information on visitor behavior can be used to modify existing exhibits to better address visitor behavior patterns. Likewise, case studies such as this provide information for application at other institutions [Marcellini and Jenssen, 1988] and can draw attention to particularly successful or unsuccessful exhibit components, which can be useful in the development of new exhibits [Wilson et al, 2003]. Finally, case studies from a variety of institutions allow conclusions about zoo visitors as a whole to be made [Bitgood et al, 1988;Serrell, 1997].…”
Section: Introductionmentioning
confidence: 97%